An Analysis of Reading Comprehension Sub-Skills in EFL Textbooks - Yihun Birhanu Aynalem; Alamirew Gebremariam Tesmand (Universitas Pendidikan Mandalika, 2023)
The aim of this research was to investigate the reading comprehension sub-skills Ethiopian EFL textbooks teach in high schools. A descriptive case study was the design of the study, for it acknowledges the sociocultural viewpoint of reading instruction which is characterized by the roles culturally produced mediating artifacts (textbooks) have on students learning opportunities. To this end, reading comprehension questions were the data collected from grade eleven and grade twelve EFL textbooks which were selected drawing on the purposeful sampling technique. A checklist of comprehension sub-skills modified from Barrett’s reading comprehension taxonomy was the data collection instrument. The data collected were analyzed using the descriptive content analysis method. Along with the two researchers, the study involved an inter-rater in order to augment the reliability of the results. He was selected among the English staff based on a random sampling technique. The findings of the research indicated that the comprehension questions of the instructional materials are characterized by the initiations of a preponderance of text-based comprehension sub-skills in general and recognition of comparison and details sub-skills in particular. Additionally, the textbooks do not ask all sub-skills of the comprehension levels except those residing in the literal comprehension. The study also found out that the questions do not teach the comprehension levels in line with their difficulty sequence. Based on the findings, it is stipulated that material designers of grades eleven and twelve EFL textbooks should keep the order of reading comprehension categories and balance the distribution of sub-skills within the comprehension levels while preparing comprehension questions for grades eleven and twelve EFL textbooks.